The Necessity for Google Slide-Based Module Development Training for High School Teachers - Andreas; Mawardi; Yari Dwikurnaningsih (Universitas Pendidikan Ganesha, 2022)
Pedagogic competence and professional competence are essential for teachers as assets to be able to present quality learning, especially in developing lesson plans. Without the two competencies, learning becomes less qualified. This research was conducted to analyze the training process and its materials, including the drawbacks and benefits. This is descriptive qualitative research. The subject of this study consists of LPMP administrators, school principals, and high school teachers. The data collection method uses the techniques of documentation studies and in-depth interviews. The data was analyzed through the triangulation technique. The results of this study indicate that the training carried out for high school teachers to improve abilities and competencies to present quality learning and education through the preparation of lesson plans follows applicable curriculum standards. The drawbacks include a limited opportunity for the participants to attend training or workshops, unavailability of teaching materials or reading references, inappropriate materials presentation in the form of PowerPoint slides, printouts or soft copies, and ineffective methods or strategy implementation. Therefore, such problems can be overcome by developing and procuring adequate training and teaching materials.